Morphometric fingerprints and downslope evolution in bathymetric surveys: insights into morphodynamics of the Congo canyon-channel - Hasenhündl, Martin; Talling, Peter J.; Pope, Ed L.; Baker, Megan L.; Heijnen, Maarten S.; Ruffell, Sean C.; da Silva Jacinto, Ricardo; Gaillot, Arnaud; Hage, Sophie; Simmons, Stephen M.; Heerema, Catharina J.; McGhee, Claire; et al. (Frontiers in Earth Science, 2024)
Submarine canyons and channels are globally important pathways for sediment, organic carbon, nutrients and pollutants to the deep sea, and they form the largest sediment accumulations on Earth. However, studying these remote submarine systems comprehensively remains a challenge. In this study, we used the only complete-coverage and repeated bathymetric surveys yet for a very large submarine system, which is the Congo Fan off West Africa. Our aim is to understand channel-modifying features such as subaqueous landslides, meander-bend evolution, knickpoints and avulsions by analyzing their morphometric characteristics. We used a new approach to identify these channel-modifying features via morphometric fingerprints, which allows a systematic and efficient search in low-resolution bathymetry data. These observations have led us to identify three morphodynamic reaches within the Congo Canyon-Channel. The upper reach of the system is characterized by landslides that can locally block the channel, storing material for extended periods and re-excavating material through a new incised channel. The middle reach of the system is dominated by the sweep and swing of meander bends, although their importance depends on the channel’s age, and the time since the last up-channel avulsion. In the distal and youngest part of the system, an upstream migrating knickpoint is present, which causes multi-stage sediment transport and overspill through an underdeveloped channel with shallow depths. These findings complement previous less-detailed morphometric analyses of the Congo Canyon-Channel, offering a clearer understanding of how submarine canyon-channels can store sediment (due to channel-damming landslides, meander point bars, levee building due to overspill), re-excavate that sediment (via thalweg incision, meander propagation, knickpoint migration) and finally transport it to the deep sea. This improved understanding of the morphodynamics of the Congo Canyon-Channel may help to understand the evolution of other submarine canyon-channels, and assessment of hazards faced by seabed infrastructure such as telecommunication cables.